Nutritional avaliation and DRIS indices in Pinus taeda L. stand subject to the NPK fertilization - Vogel, Hamilton Luiz Munari; Schumacher, Mauro Valdir; Lima Neves, Júlio César (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
In Brazil, the Diagnosis and Recommendation Integrated System (DRIS) has already been widely used as a tool for nutritional management in Eucalyptus stands, with pure studies currently carried out with Pinus. Thus, the work had as main objective to perform a nutritional evaluation by the DRIS in Pinus taeda L. stand, at 19 months of age, planted in Humic Cambisol aluminium in “Campos de Cima da Serra”, region Rio Grande do Sul State, Brazil. A total of 64 doses of N (Urea), P2O5 (triple superphosphate) and K2O (potassium chloride) were used for the three-factor confounding technique. Three needles-composed samples were collected from each of the treatments (each sample consisting of three trees), determining the mean levels of N, P, K, Ca and Mg. For the calculation of DRIS functions, the formula f = (R - r) / s, where: f = function value for the (X / Y) ratio between the contents of two nutrients; R = value of the dual relation (X / Y); r = mean value of the dual relations (X / Y); s = standard deviation of the dual relations (X / Y). The results pointed that N and Ca elements were the limitant nutrient to tree growth, by DRIS evaluation, indicating the limit sequence below: N = Ca > Mg > K > P; the contents of N, P, K, Ca e Mg estimated by the critical graphic level were of 14.6, 1.6, 8.7, 2.6 and 0.8 g kg-1 respectively, indicating good nutritional conditions of Pinus taeda plants.